Convective air drying characteristics of thin layer carrots - Doymaz, I (ELSEVIER SCI LTD, 2004)
The effects of air temperature, air-flow rate and sample thickness on drying kinetics of carrot cubes were investigated. Convective air drying characteristics of carrot cubes were evaluated in a cabinet dryer. Drying was carried out at 50, 60, 65, 70 degreesC and drying data were analyzed to obtain diffusivity values from the period of falling drying rate. In the falling rate period, moisture transfer from carrot cubes was described by applying the Fick's diffusion model, and effective moisture diffusion coefficients were calculated. Effective diffusivity increased with increasing temperature. An Arrhenius relation with an activation energy value of 28.36 kJ/mol expressed effect of temperature on the diffusivity. Two mathematical models available in the literature were fitted to the experimental data. The Page model is given better prediction than the Henderson and Pabis model and satisfactorily described drying characteristics of carrot cubes. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: carrot; drying; rehydration; mathematical modelling; diffusivity; activation energy; MICROWAVE; SIMULATION; SLICES; FOODS; PRETREATMENTS; DEHYDRATION; DIFFUSION; APRICOTS; QUALITY; MODEL; Engineering; Food Science & Technology